Pressure driven rotational isomerism in 2D hybrid perovskites - Yin, Tingting (2023)
Multilayers consisting of alternating soft and hard layers offer enhanced toughness compared to all-hard structures. However, shear instability usually exists in physically sputtered multilayers because of deformation incompatibility among hard and soft layers. Here, we demonstrate that 2D hybrid organic-inorganic perovskites (HOIP) provide an interesting platform to study the stress-strain behavior of hard and soft layers undulating with molecular scale periodicity. We investigate the phonon vibrations and photoluminescence properties of Ruddlesden-Popper perovskites (RPPs) under compression using a diamond anvil cell. The organic spacer due to C4 alkyl chain in RPP buffers compressive stress by tilting (n = 1 RPP) or step-wise rotational isomerism (n = 2 RPP) during compression, where n is the number of inorganic layers. By examining the pressure threshold of the elastic recovery regime across n = 1-4 RPPs, we obtained molecular insights into the relationship between structure and deformation resistance in hybrid organic-inorganic perovskites.